Female neurogenic stress urinary incontinence. Issue 4 (July 2020) - Farag, Fawzy; Doherty, Ruth; Arlandis, Salvador
Abstract : Purpose of review: The aim of this article is to look into recent updates on the management of neurogenic stress urinary incontinence (NSUI) in adult females. Recent findings: Recently, a small number of studies have investigated different surgical modalities in treatment of NSUI in adult females including artificial urinary sphincter (AUS), suburethral tapes (SUT) and adjustable slings and urethral bulking agents. Up to 70% of neurogenic patients who received AUS implants are continent and have not required surgical revision over a 20-year follow-up period. However, the risk for explantation of AUS may be twice as high in neurogenic patients compared with nonneurogenic patients. SUT have success and improvement in quality of life rates of up to 52 and 68%, respectively. However, complications may be as high as 24%. Early data on adjustable slings may suggest up to 80% continence with low complication rates. Summary: AUS can provide satisfactory continence levels with acceptable rates of revision and explantation. SUT are effective but more than half of patients may require additional procedures. Adjustable slings could be a promising option. Further high-quality studies with careful attention to methodology and standardization of both definitions used and outcome reporting are required to help us reach safe conclusions.